PENYULUHAN DAN DEMONSTRASI PENGOLAHAN AIR BERSIH PADA SUKU ANAK DALAM (SAD) LUBUK KAYU ARO - Lili Andriani; Susi Widiawati; Yuliawati Yuliawati (Universitas Muhammadiyah Tapanuli Selatan, 2019)
The availability of clean water is a major human requirement. Suku Anak Dalam community communities often struggle to access clean water sources. The river becomes one of the sources of clean water used to meet the needs of water, but the condition of the river does not meet the standard for use. The purpose of this community devotion is to do clean water counseling and demonstration about the manufacture of water filter media in Suku Anak Dalam in Lubuk Kayu Aro, Mestong District of Muaro Jambi, Jambi. This activity will be expected to improve the health quality of the Suku Anak Dalam in Lubuk Kayu Aro. The method used was counseling to the community of Suku Anak Dalam in Lubuk Kayu Aro and did a demonstration of a simple water filter media. Materials needed include sieve containers, bottled water, gravel, palm-fiber, sand, and foam. The result of this community devotion is increasing public knowledge about the importance of clean water in life. In addition, people can know how to create water filter media and apply it in daily life. Keywords: clean water, Suku Anak Dalam, water filter media